Islamic Boarding Schools in Indonesia: Caring for Nationalism and Preventing Radicalism - Selvia , Lena Selvia; Sunarso (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to analyze the values of nationalism materials in Islamic boarding schools. So far there has been a judgement believing that Islamic boarding schools are the center of radicalism in Indonesia. The militancy and aggressiveness of radicals are considered as the impact of education carried out in Islamic boarding schools. This study refutes research findings that assess Islamic boarding schools as the basis of radicalism. Through a study of the curriculum, books and teachings carried out in Islamic boarding schools, as well as the values of nationalism and tolerance, this research was carried out with work principles and library research methods. The data is collected from literature, especially the results of research, scientific publications and developing discourses related to pesantren and nationalism. The results of this study indicate that radicalism and terrorism do not develop in Islamic boarding schools. Instead of teaching radicalism and terrorism, the teachings in pesantren shave become the seed of the nationalism. Historical traces show that pesantren are an important part of the birth of the state, becoming a stronghold against colonialism. In the context of a multi-cultural, racial and religious nation, Islamic boarding schools not only teach the value and direction of religion, but also become a strategic media in instilling nationalism values, respecting each other and respecting differences, among persons with the same faith, and even to non-Muslims.